Market Profile Analysis of Lokawisata Baturraden - Widiarrachman, R. Fajar; Rahtomo, Wisnu; Putri, Athirah Salsabila S; Annisa, Ghina Nur; Wicaksono, Mochamad Arif; Nareswari, Nadhira; Sakti, Nauval Pramodya; Lathifa, Putri H; Ningtyas, Wulanndari Ayu (Journal of Tourism, Hospitality and Travel Management, 2023)
This research studies segmentation and targeting strategies at Lokawisata Baturraden, Banyumas Regency, Central Java Province. This study uses the theory of destination market segmentation, whose indicators consist of demography, geography, psychography, and behavior. Then the research results are also strengthened by targeting theory which explains targeting as a process of evaluating segmentation and focusing marketing strategies on a group of people with the potential to become respondents. Data collection methods were used in the form of questionnaires and interviews. Then the data obtained is processed using SPSS software with frequency and crosstab calculations. The results obtained will be recommendations for developing potential target market strategies.